2008
DOI: 10.1016/j.jas.2007.06.001
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study into the effects of X-ray and computed tomography exposure on the amplification of DNA from bone

Abstract: Grieshaber, Britta M.; Osborne, Daniel L.; Doubleday, Alison F.; and Kaestle, Frederika A., "A pilot study into the effects of X-ray and computed tomography exposure on the amplification of DNA from bone" (2008). Anthropology Faculty Publications. 32.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 25 publications
0
38
0
Order By: Relevance
“…They used measurements of surface area and volume from human crania to illustrate the validity of this technology [3]. They stated that there are many advantages of laser scanners over other types of 3D imaging technology in terms of cost, speed, and portability [43]. Numerous studies done in the past found it to be very useful in orthodontics to analyze growth, softtissue changes, treatment simulation, appliance designs and treatment effects in three-dimensions [1,37,44,45,47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They used measurements of surface area and volume from human crania to illustrate the validity of this technology [3]. They stated that there are many advantages of laser scanners over other types of 3D imaging technology in terms of cost, speed, and portability [43]. Numerous studies done in the past found it to be very useful in orthodontics to analyze growth, softtissue changes, treatment simulation, appliance designs and treatment effects in three-dimensions [1,37,44,45,47].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies done in the past found it to be very useful in orthodontics to analyze growth, softtissue changes, treatment simulation, appliance designs and treatment effects in three-dimensions [1,37,44,45,47]. In addition, the spatial resolution of 3D models produced by laser scanners is equal to or greater than many 3D models produced under standard clinical conditions by CT and MRI machines [43]. Aung et al [32] also compared laser surface scanning to direct anthropometry, but they used living subjects.…”
Section: Discussionmentioning
confidence: 99%
“…17 Recent work has shown that radiation of fossils may have a detrimental effect on ancient DNA when the total surface dose exceeds 200 Gray, so these researchers recommended using as low a dose as possible when scanning fossils as well as using resolution no higher than necessary to achieve the desired outcome. 18 The value of 200 Gray is far higher than any dose from a XCT or µXCT scan (8000 times higher than the highest dose for a medical CT scan).…”
Section: Research Articlementioning
confidence: 99%
“…Archaeologists and/or curators can provide important information concerning pre-and post-excavation processes, such as exposure to sunlight, moisture conditions, treatment with preservatives, and even the use of X-rays or CT imaging; all of which can damage the residual DNA in a specimen. Even the physical distribution of material to different laboratories can cause an unexpected hazard, such as exposure to ionizing radiation, which is known to reduce the amount of amplifiable DNA (Götherström 1995;Grieshaber 2008). Specimens can be exposed to radiation if sent by airmail.…”
Section: Following a Careful Protocolmentioning
confidence: 99%
“…While often critical to the diagnostic process, using noninvasive sampling techniques such as X-ray, CAT scan and/or magnetic resonance imaging (MRI) can damage residual DNA in the remains. X-ray techniques, for instance, have the highest irradiation energy and are likely to damage fragile aDNA (Grieshaber 2008). If imaging of the pathological lesion is conducted, especially using an X-ray, sampling the specimens prior to irradiation is recommended.…”
Section: Diseases Of the Past And Adna Studiesmentioning
confidence: 99%